2019
DOI: 10.1007/s11136-019-02364-w
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents with VACTERL association: health-related quality of life and psychological well-being in children and adolescents and their parents

Abstract: Purpose VACTERL association is a rare and complex condition of congenital malformations, often requiring repeated surgery and entailing various physical sequelae. Due to scarcity of knowledge, the study aim was to investigate self-reported health-related quality of life (HRQoL), anxiety, depression and self-concept in children and adolescents with VACTERL association and self-reported anxiety and depression in their parents. Methods Patients aged 8-17 years with VACTERL association and their parents were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…A literature review by van Oers et al (2014) found that child's medical characteristics, such as child's age or the severity of illness, were not related to parental anxiety or depression in parents of chronically ill children. However, studies specifically on EA have suggested that child's age (Faugli et al, 2009;Kassa et al, 2020;Witt et al, 2019), EA severity (Witt et al, 2019), associated anomalies (Rozensztrauch et al, 2020), and feeding problems (Dellenmark-Blom et al, 2015;Rozensztrauch et al, 2020) might have an impact on parental mental health or family functioning. The current study partly supported the findings by van Oers et al (2014), as statistically significant differences were not found in the levels of parental anxiety or depression between child's age, or EA complexity sub-groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review by van Oers et al (2014) found that child's medical characteristics, such as child's age or the severity of illness, were not related to parental anxiety or depression in parents of chronically ill children. However, studies specifically on EA have suggested that child's age (Faugli et al, 2009;Kassa et al, 2020;Witt et al, 2019), EA severity (Witt et al, 2019), associated anomalies (Rozensztrauch et al, 2020), and feeding problems (Dellenmark-Blom et al, 2015;Rozensztrauch et al, 2020) might have an impact on parental mental health or family functioning. The current study partly supported the findings by van Oers et al (2014), as statistically significant differences were not found in the levels of parental anxiety or depression between child's age, or EA complexity sub-groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Witt et al (2019) found that the parents of younger children born with EA (aged 2-7 years) reported lower mental health compared to the parents of older children and adolescents. In another study, parents of older children and adolescents (aged 8-17) born with VACTERL association self-reported anxiety and depression at levels that were comparable to a non-clinical sample (Kassa et al, 2020). These findings would suggest that parental mental health might improve over time, whilst the child born with EA grows and develops through childhood into adolescence.…”
Section: Introductionmentioning
confidence: 90%
“…In other Swedish studies, children with VACTERL (stands for Vertebral defects, Anal atresia, Cardiac defects, Tracheo-esophageal fistula, Renal anomalies, and Limb abnormalities. Individuals diagnosed with VACTERL association have at least three of these characteristic features) reported psychological well-being which was comparable to the norm group of Swedish school children [ 55 ] and intelligence was within the normal range [ 56 ]. However, attention difficulties were found in eight out of ten preschool children with VACTERL, requiring adjustments at school, and two of these were later diagnosed with attention deficit hyperactivity disorder [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after the multivariable regression analysis, these clinical variables were not retained as a part of the multifactorial model. Previous research has shown that associated anomalies in children with EA negatively impact family functioning [ 24 ] while parents of children with VACTERL association (i.e., with at least three of the following: vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, limb abnormalities) self-report levels of anxiety and depression comparable to non-clinical samples [ 38 ].…”
Section: Discussionmentioning
confidence: 99%